(untitled) (Agora for Physical Education and Sport, 2019)
Parental behaviors play a key role in the acquisition of habits and customs by their 1 to 4 years old children. This paper aims to explore children’s habits towards play and movement. To do so, we’ve used the Comprehensive Early Childhood Parenting Questionnaire (CECPAQ), specifically the items related to the domain of stimulation. Data suggest that particular parental behaviors tend to stimulate and favor children’s play during those early ages; however, some differences have been found in relation to gender (favorable to children) and to the (higher) level of urbanization.